RISK OF CONGENITAL HEART DISEASE IN FETS AND CHILDREN CONCEIVED THROUGH ASSISTED REPRODUCTION TECHNOLOGIES: A SYSTEMATIC REVIEW - Lobo, Aída Maria Ferrário de Carvalho Rocha (2024)
Introduction: Congenital heart disease (CHD) is characterized by structural and functional abnormalities of the cardiovascular system, which may or may not be related to environmental factors. Risk factors for CHD include hereditary and non-hereditary causes, among which the role of assisted reproductive technologies (ART) remains controversial. Objective: To evaluate the risk of CHD in fetuses, infants and children conceived by In Vitro Fertilization (IVF) and Intracytoplasmic Sperm Injection (ICSI), compared to those conceived spontaneously. Materials and Methods: This study consists of a systematic review of observational studies, through electronic searches in the following databases: MedLine via Pubmed, LILACS via BVS, Cochrane library, Scopus via CAPES. Results: Ten studies were identified for review, including 07 cohort studies and 03 case-control studies. Of these, 7 stated that singleton fetuses, infants and children conceived by IVF/ICSI have a higher risk of congenital heart disease than those conceived naturally (0.7%-2.1%). Five stated that ART was associated with a higher risk of Tetralogy of Fallot (TF). Conclusion: The present study demonstrates that singleton fetuses, infants and children conceived by IVF/ICSI have a higher risk of CHD than those conceived naturally. In this sense, an increased frequency of CHD was observed after ART with a heterogeneous spectrum of cardiac anomalies, mainly major defects, the most frequent being TF, Septal Heart Defects (SCD) and Patent Ductus Arteriosus (PDA). This higher risk of CHD does not vary according to the ART method.